ЁШЛАРНИ МИЛЛИЙ ҲУНАРМАНДЧИЛИККА ОИД КАСБ ТАНЛАШГА ЙЎНАЛТИРИШНИНГ ТАЪЛИМИЙ ВА ТАРБИЯВИЙ АҲАМИЯТИ - Пахратдинова, Р.О. (SCIENCE and SOCIETY, 2021)
The article emphasizes the educational and pedagogical importance of the development of physical preparation of students, their acquaintance with the world and people of labor, tools and methods, key industries and professions, the use of tools, the development of working skills in the manufacture of simple objects and a conscious choice of career.